Analisis Kebutuhan Pengembangan Lembar Kerja Peserta Didik Berbasis STEM dalam Aplikasi Android - Rahmayani, Fadillah; Hendri, Menza; Rasmi, Dian Pertiwi (Universitas Halu Oleo, 2021)
This research go to analyze the initial needs of teachers and students for the development of learning media in the form of STEM-based student worksheet applications in circular motion. Data obtained through observation, interviews and student learning style questionnaires given to teachers and students of SMA N 1 Muaro Jambi. Teachers need an attractive and interactive learning media that can attract students' interest, while students need learning media that combines all aspects of visual, audiotorial and kinesthetic learning styles where it is obtained from a questionnaire th at students have visual, kinesthetic and audiotorial learning styles with a percentage of 58, 3%, 58.3% and 52.8%. So that researchers will develop student worksheets in the form of android based on the results of the learning style analysis. Products produced are in the form of android and based on STEM.